Reduction of NOx Emission from Gas TURBINE COMBUSTOR Applying Fuel-Staged Combustion - Mohammad Nazri; Mohd Jaafar (ASEAN Journal of Chemical Engineering, 2002)
A two-stage lean/lean gas turbine combustor was developed with low NOx characteristics in each stage using a small radial swirler of 40-mm outlet diameter in the pilot stage. Both flame tubes were arranged in series with the smaller combustor (76 mm inside diameter) as the pilot stage and the larger combustor (140 mm inside diameter) as the main stage. The pilot stage was fuelled via vane passage fuel injector, while the main stage was fuelled around the wall of the exit plane of the pilot stage, using wall fuel injectors. Low NOx emissions were obtained when using fuel staging for methane fuel, as low as 6 ppm. A NO. reduction of more than 40 % was obtained at equivalence ratio of near 0.7, when using fuel staging compared to the non-fuel-staging test. Tests were conducted using methane as fuel. This was achieved at very small increase in carbon monoxide emissions especially near the rich region and with almost no increase at all in the unburned hydrocarbon emissions at the same equivalence ratio.